Multispecies bacterial bio-input: tracking and plant-growth-promoting effect on Lettuce var. sagess - Vio, Santiago Adolfo (2023)
The use of multispecies bacterial bio-inputs is a promising strategy for sustainable crop production over the use of single-species inoculants. Studies of the use of multispecies bio-inputs in horticultural crops are scarce, not only on the growth-promoting effects of each bacterium within the formulation, but also on their compatibility and persistence in the root environment. In this work, we described that a multispecies bacterial bio-input made up of Azospirillum argentinense Az39, Gluconacetobacter diazotrophicus PAL-5, Pseudomonas protegens Pf-5 and Bacillus sp. Dm-B10 improved lettuce plant growth more effectively than when these strains were inoculated as single-species bio-inputs. Bacteria persisted together (were compatible) and also colonized seedling roots of lettuce plants grown in controlled conditions. Interestingly, colonization was highly related to an early and enhanced growth of seedlings grown in the nursery. A similar effect on plant growth was found in lettuce plants in a commercial greenhouse production in the peri-urban area of La Plata City, Buenos Aires, Argentina. To our knowledge, this is the first study demonstrating that a synthetic mixture of bacteria can colonize and persist on lettuce plants, and also showing their synergistic beneficial effect both in the nursery greenhouse as well as the commercial production farm.